CLONING AND CHARACTERIZATION OF TWO EcR ISOFORMS FROM JAPANESE PINE SAWYER, Monochamus alternates. Issue 1 (6th August 2013) - Weng, Hongbiao; Shen, Weifeng; Liu, Yan; He, Lihua; Niu, Baolong; Meng, Zhiqi; Mu, Jianjun
<x xml:space="preserve">Abstract</x> The ecdysone receptor (EcR) is the hormonal receptor of ecdysteroids, which regulates insect growth and development. In this study, we cloned and characterized two isoforms of EcR in Monochamus alternates named MaEcR A and MaEcR B. The cDNAs of MaEcR A and MaEcR B have open repeating frames of 1, 695 and 1, 392 bp, respectively. The deduced proteins have the same C‐terminal sequence and varied in N‐terminal, and are consistent with reports on other insect species, particularly with the receptor of another coleopteran, Tribolium castaneum. The isoform‐specific developmental expression profile of EcR in the epidermis and the midgut were analyzed with quantitative real‐time reverse‐transcriptase polymerase chain reaction in the pupal stage. RNA interference (RNAi) with common or isoform‐specific regions induced developmental stagnation. When treated in the later larval stage, RNAi with either the common sequence or an EcR A specific sequence caused more severe effects and most larvae died prior to adulthood. The EcR B specific sequence caused less severe effects and about half of the treated larvae became adults, but some showed developmental defects. RNAi with both isoforms at early pupal stage attenuated the expression of 20E‐regulated genes E74, E75, and HR3. The study demonstrates the role of EcR in the transduction of ecdysteroid response in Monochamus alternatus.